Exhaled nitric oxide and mannitol test to predict exercise‐induced bronchoconstriction. Issue 8 (29th August 2018) - Kim, Kyubo; Cho, Hong Je; Yoon, Jung Won; Choi, Sun Hee; Sheen, Youn Ho; Han, Man Yong; Baek, Heysung
Abstract: Background: Exercise‐induced bronchoconstriction (EIB) is diagnosed via exercise challenge on a treadmill, but such testing requires complex equipment and sufficient health‐care resources. The fraction of exhaled nitric oxide (FeNO) test and mannitol bronchial provocation test (BPT) may serve as a surrogate for exercise testing. Methods: We compared the diagnostic utilities of the FeNO test and mannitol BPT in predicting EIB in asthmatic children. We retrospectively analyzed data from 60 asthmatic children aged 6–16 years. We compared the exercise BPT results, FeNO levels, and mannitol BPT data. Results: All subjects were divided into exercise‐positive ( n = 41) or ‐negative ( n = 19) BPT groups. Of the 41 exercise‐positive patients, 32 were mannitol BPT positive and nine were mannitol BPT negative. Of the 19 exercise‐negative patients, nine and 10, respectively, were mannitol BPT positive and BPT negative. The maximum % forced expiratory volume in 1 s (FEV1 ) decrease after exercise was positively correlated with FeNO ( r = 0.556, P  < 0.001), and with mannitol response–dose ratio (RDR; r = 0.416, P = 0.001). The receiver operating characteristic (ROC) curve for FeNO to discriminate between asthmatic subjects with and without EIB had an area under the curve (AUC) of 0.771 (95%CI: 0.643–0.870). The discriminatory ROC curve for mannitol RDR had an AUC of 0.763 (95%CI: 0.633–0.864). The AUC of FeNO and mannitol RDR did not differ significantly. Conclusions: EIB significantly correlated with both FeNO and mannitol BPT data. Given that both methods similarly predicted EIB in asthmatic children, the simpler and safer FeNO test alone may be a clinically useful diagnostic tool.